(untitled) (Biocenosis, 2022)
The designing of the farms is a valuable tool to be able to adapt to the processes of change and make decisions that combine economic, and social issues, as well as the biological nature of the agricultural activity and the effect of the climate phenomena that occur nowadays. This article describes how to implement a management plan for agricultural farms from a comprehensive approach, considering the climatic, climate, risk, and edaphic variables analysis as the basis for the designing of farm plans that have a vision of sustainable development, management of risk and conservation of soil and water resources. Se definen cuatro fases para desarrollar un plan de manejo integral: diagnóstico, planificación, gestión y seguimiento de la herramienta como base para la planificación y utilización racional de las tierras para la actividad agropecuaria, lo cual permite adecuarse dependiendo de las prácticas agro-conservacionistas que pueden cumplir con los objetivos de producción y que pueden ser adaptadas a los sistemas de cada finca. Four phases are defined to develop a comprehensive management plan: diagnosis, planning, management, and monitoring of the tool as a basis for the planning and rational use of land for agricultural activity, allowing it to be adapted depending on the agro-conservationist practices to meet the production objectives and the systems of each farm.